2022
DOI: 10.1186/s13020-022-00617-4
|View full text |Cite
|
Sign up to set email alerts
|

Developing an artificial intelligence method for screening hepatotoxic compounds in traditional Chinese medicine and Western medicine combination

Abstract: Backgrounds Traditional Chinese medicine and Western medicine combination (TCM-WMC) increased the complexity of compounds ingested. Objective To develop a method for screening hepatotoxic compounds in TCM-WMC based on chemical structures using artificial intelligence (AI) methods. Methods Drug-induced liver injury (DILI) data was collected from the public databases and published literatures. The total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Chen et al . 198 , for example, constructed a model using ML to screen for hepatotoxic components among many compounds in TCM.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al . 198 , for example, constructed a model using ML to screen for hepatotoxic components among many compounds in TCM.…”
Section: Discussionmentioning
confidence: 99%
“…To predict toxicity or side effects, Liu et al used a previously developed framework and a deep learning method to predict toxicity or side effects to evaluate the safety of TCM prescriptions recommended for COVID-19 treatment in China [54]. Chen et al developed a machine learning-based method for screening hepatotoxic compounds in TCM and Western medicine combinations, utilizing algorithms like support vector machines, neural networks, decision trees, and random forests [55]. In recent years, several successful AI models, including DeepHit, FP-ADMET, and ResNet18DNN, have been used to predict the toxicity properties of compounds like hERG, LD50, DILI, Ames mutagenesis, carcinogenesis, skin sensitization, and Tox21 assay endpoints [56].…”
Section: Traditional Chinese Medicine Prescriptions Holistic Optimiza...mentioning
confidence: 99%
“…Their work helped screen potential hepatoprotectants from natural products. Chen [ 59 ] developed a method for screening hepatotoxic compounds in TCM and Western medicine combinations on the basis of chemical structures by using SVM, neural networks, DT, and RF. Their results showed that RF yielded a classification accuracy of 0.838, which was better than other machine learning methods.…”
Section: Applications Of Machine Learning In Tcm Researchmentioning
confidence: 99%
“…Natural product development Deep neurol network [47,50], RF [53,54,58,59,93], SVM [51,53,54,57,59,93], DT [59,93], neural network [53,59] RF was better than SVM, neurol network and DT in screening hepatotoxic compounds [59]. RF model is more accurate than SVM and DT in identifying molecular characteristics of natural product compounds with the meridians of TCM [93] Disease diagnosis SVM [10,61,66,[81][82][83], DT [68,[81][82][83], neural network [45, 61-63, 65, 82, 83], RF [61,64,67,82,83], CNN [64,67,[70][71][72][73][74][75][76][77][78]81], RNN…”
Section: Performance Of the Algorithmmentioning
confidence: 99%